2019
DOI: 10.1101/gad.319194.118
|View full text |Cite
|
Sign up to set email alerts
|

Afadin cooperates with Claudin-2 to promote breast cancer metastasis

Abstract: Claudin-2 promotes breast cancer liver metastasis by enabling seeding and early cancer cell survival. We now demonstrate that the PDZ-binding motif of Claudin-2 is necessary for anchorage-independent growth of cancer cells and is required for liver metastasis. Several PDZ domain-containing proteins were identified that interact with the PDZ-binding motif of Claudin-2 in liver metastatic breast cancer cells, including Afadin, Arhgap21, Pdlim2, Pdlim7, Rims2, Scrib, and ZO-1. We specifically examined the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 58 publications
(106 reference statements)
2
40
1
Order By: Relevance
“…Tabariès and co-workers showed that afadin, an actin filament-binding protein, might create a complex with claudin-2 that enables the efficient formation of metastases. The results revealed the possibility of using a combination of claudin-2 and afadin as prognostic markers that may allow better detection of metastatic potential [110].…”
Section: Claudins In Breast Cancermentioning
confidence: 95%
“…Tabariès and co-workers showed that afadin, an actin filament-binding protein, might create a complex with claudin-2 that enables the efficient formation of metastases. The results revealed the possibility of using a combination of claudin-2 and afadin as prognostic markers that may allow better detection of metastatic potential [110].…”
Section: Claudins In Breast Cancermentioning
confidence: 95%
“…Afadin is a cytoplasmic actin-filament-binding protein responsible for the formation and stabilization of tight and adherens junctions [192][193][194][195]. Marques et al (2018) observed that infection by H. pylori lowered the expression of Afadin protein independently of CagA and VacA in MKN74 and NCI-N87 cell lines [196].…”
Section: Afadin Protein Downregulationmentioning
confidence: 99%
“…This PDZ-binding motif was shown to associate with a variety of TJ plaque scaffold proteins including the membrane-associated guanylate kinase (MAGUK) family adapters ZO-1-3 [45] (Figure 1). Recently, Tabaries et al identified several new candidate claudin-2 binding partners [34]. These will be described in more detail in Section 4.4.…”
Section: Properties Of Claudin-2mentioning
confidence: 99%